Odpowiedzi

2010-02-10T14:05:20+01:00
(3x ×1)+(-x+ 3) = 3x -x +3 = 2x+3
(-8a+4)-(2a+7) = -8a+4-2a-7 = -10a -3
5razy(2x-3y)-(-y-x) = 10x-15y +y+x = 11x -14y
-1(5-6a)+(a-2)= -5+6a +a -2 = -7+7a
-0,5(8a+4b)+(-a-b) = -4a - 2b -a -b = -5a-3b
7x³-14y)÷7 = x³ -2y
⅓(-3x²+6y³-9) = -x² + 2y³ - 3
2010-02-10T14:09:49+01:00
3x-x+3=3+2x
-8a+4-2a-7=-3-10a
10x-15y+y+x= 11x-14y
-5+6a+a-2=-7+7a
-4a-2b-a-b=-5a-3b
7x³-2y
-x²+2y²-3














2010-02-10T14:12:32+01:00
(3x ×1)+(-x+ 3)= -3x² + 9x - x +3 = -3x² + 8x +3
(-8a+4)-(2a+7) = -16a² + 56a + 8a - 28 = -16a² + 64a - 28
5razy(2x-3y)-(-y-x) = 5 ( 2xy + 2x² - 3y² - 3xy ) 5( -xy + 2x²- 3y²) = -5xy + 10x² -15xy
-1(5-6a)+(a-2)= -1( 5a - 10 - 6a² + 12a) = -1( -6a² + 17a - 10) = 6a² - 17a +10
-0,5(8a+4b)+(-a-b)= -0,5( - 8a² - 8ab - 4ab - 4b²) = -0,5 ( -8a² - 4b² - 12ab) = 4a² + 2b² + 6ab
⅓(-3x²+6y³-9) = -x² + 2y³ - 3



POZDRAWIAM ;*